The age of revival as a crossroad in Bosnian Muslim literature and culture - Rizvić, Muhsin (Anali Gazi Husrev-Begove biblioteke, 2001)
Towards the end of Sixties and in the early Seventies in 19th Century, the emergence of the newspapers Sarajevski cvjetnik /The Flower Garden from Sarajevo/ announced the movement of people's awakening of Bosnian Moslem national/ethnic spirit that would last in the course of the next three decades. Mehmed Šaćir Kurtćehajić in a series of editorials in this newspapers, which had been printed simultaneously and concurrently in two versions, in the local language in Cyrillic alphabet and in Turkish in a special type of Bosnian script arebica, having written on a literary work in the newspapers, on the halt of domestic cultural affairs and life, and on patriotism, wrote a salute to "the new age" and "the new constitutions" that this age was going to bring forward with it. In the course of Eighties and Nineties in the last century, the Bosnian Moslem literary and cultural revival movement gradually matured having been founded on the people's creative accomplishments. Simultaneously with the literary and cultural transformation, the transformation of the national name was also taking place. The name Bosniak gradually faded away in the period, and the religious name "Moslem" became much stronger. Besides, an opposition movement for religious and educational autonomy emerged as an expression of resistance and political struggle against the Austro-Hungarian occupation. This movement would later become the first national and political party of the Moslem people under the name Muslimanska narodna organizacija (The Moslem National Organization). This fact speaks enough about the Bosnian Moslems as a political nation in the modern sense of the word. A number of educational, social and civic institutions, societies, organizations and magazines, such as Behar, Biser, and others have been established. The Bosnian Moslem literary and cultural revival can be limited to the period starting in 1887 and the emergence of Narodno blago /People's Treasury/ by Mehmed beg Kapetanović. It continued during the era of Behar, and it ended in 1918, when the last issue of Biser was published, and when the Gajret Society was also active. This movement was based on the backdrop of mother tongue and national values with the aspiration to express the ethnic specificity and independence of Bosnian Moslems as the Southern Slavic nation between the Serbs and the Croats. The second characteristic worth mentioning is that the writers of revival period, without exception, had come from the circles of secular, laic and civic intelligentsia. This literature consisted of printed works, as opposed to the previous ones, which had been kept in manuscripts. The new literature was available to anyone ready to learn both Latin and Cyrillic Alphabets. This was the reason for this literature to find its ways into families and people in general. The strong presence and influence of national oral poetry in the written forms of literature was quite evident. Bosnian language as the means of literary expression was also pronounced. All these elements brought the reading public together, particularly through language, literary and social interest, and the mature literary works in the sense of national awareness that the authors from the period wrote for it.